(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This article comprehensively analyzes the role of infrastructure in the innovative development of small businesses. In particular, the influence of elements of scientific and technical, information and communication, and financial infrastructure on the activities of small business entities has been revealed. Also, the current state of infrastructure facilities, their shortcomings, and proposals and recommendations for their improvement have been developed. Based on foreign experience, the article outlines ways to further develop the infrastructure for innovative support of small businesses in Uzbekistan.